Pengaruh Financial Leverage, Operating Leverage, Struktur Modal dan Kinerja Aset Terhadap Earning Per Share - Endri Purnomo (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2022)
This study aims to examine the effect of financial leverage, operating leverage, capital structure and asset performance on earnings per share (EPS) in automotive and component companies listed on the Indonesia Stock Exchange for the 2017-2021 period. This type of research is an associative quantitative research with secondary data sources from annual reports and financial reports of companies in the automotive and component sub-sector published by the Indonesia Stock Exchange (IDX). Determination of the sample by purposive sampling method in order to obtain 55 samples. The data analysis method used is multiple linear regression analysis, the data is processed using software eviews 12. The results show that (1) financial leverage as proxied by degree financial leverage (DFL) has no significant effect on earnings per share (EPS), but has positive or unidirectional relationship, (2) operating leverage as proxied by degree operating leverage (DOL) has no significant effect on earnings per share, but has a positive or unidirectional relationship, (3) capital structure is proxied by long term debt to equity ratio ( LDER) does not have a significant effect on earnings per share, but has a positive or unidirectional relationship (4) asset performance as proxied by return on assets (ROA) has a positive and significant effect on earnings per share.